Comparison of impurity profiles of lipiblock® vs. orlistat using HPLC and LC-MS/MS - Schneider, Alex; Wessjohann, Ludger A.; Severi, Juliana A. [UNESP]; Wagner, Vilegas [UNESP] (My University, 2012)
Comparative HPLC-UV and LC-MS/MS studies of impurity profiles of a reference sample (Xenical®, F. Hoffmann-La Roche Ltd., Switzerland) vs. generic (Lipiblock®, EMS-Sigma Pharma, a generic drug) were carried out with ethanol extracts of commercial samples. The generic formulation contained higher levels of common impurities as well as a considerable number of impurities not found in the reference product. The detected impurity profile of Lipiblock® revealed that it most likely is based on fermentation. Since the effect of the impurities is unknown, at this point fully synthetic Xenical® appears to offer a better safety margin than Lipiblock® which, however, compares quite well to other generic formulations.
Keywords: Generics; HPLC-MS/MS; HPLC-UV; Orlistat; cobese; generic drug; lipiblock; orsoten; rotipuran; suprapur; tetrahydrolipstatin; unclassified drug; controlled study; drug formulation; drug impurity; drug safety; drug structure; fermentation; high performance liquid chromatography; intermethod comparison; liquid chromatography; mass spectrometry